SELF-ESTEEM COHESION AND RESILIENCE ABILITY OF A MARGINAL CHILD IN 'PÜNKTCHEN UND ANTON' ROMAN (KOHESI SELF-ESTEEM DAN KEMAMPUAN RESILIENSI ANAK MARGINAL DALAM ROMAN 'PÜNKTCHEN UND ANTON') - Lisda Liyanti; Saskia Nabila (Leksema: Jurnal Bahasa dan Sastra, 2019)
Germany nowadays is known as one of the most robust economies in Europe. Yet, at the beginning of 20th Century Germany, poverty became a severe problem that caused a social and cultural impact on the children. Positive self-esteem and resiliency in children were needed to cope with the situation. The roman titled Pünktchen und Anton, written in 1931 by Erich Kästner, describes the children’s life in Berlin dealt with the poverty problem.  This research aims to see how self-esteem and resiliency in children described as a life tool for the first figure (Anton) who classified as an adversity child in the novel. This question is answered by using descriptive qualitative method and self-esteem theory by Nathaniel Branden.  The result shows there is advocacy in describing a marginalized Anton to become a hero thank to his positive self-esteem (self-efficacy and self-respect). His positive self-esteem builts him to be resilient.